2017
DOI: 10.1177/0011128717727739
|View full text |Cite
|
Sign up to set email alerts
|

Better to Stay Home: Evaluating the Impact of Day Reporting Centers on Offending

Abstract: This article reports the findings of a quasi-experimental evaluation of community resource centers (CRCs)—nonresidential, day reporting centers employed for recent parolees. CRC participants ( n = 2,789), drawn from release cohorts in 2008, 2009, and 2010, were matched using propensity scores to similar parolees who did not participate in CRC programming ( n = 16,500). At the conclusion of the scoring and matching process, 2,789 CRC–parolee pairs were identified, including the full population of program partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…We evaluated a single DRC in a single county in a single state—what “happens in Vegas” may indeed “stay in Vegas.” Our study suggests DRCs can be effective, but it is clear from prior evaluations that DRCs are not always effective. It is not without reason that the title of a recent quasi-experimental evaluation of DRC programs in New Jersey begins with “Better to Stay Home…” (Hyatt & Ostermann, 2019). Variation across evaluations of DRCs could be due to a number of factors in addition to jurisdictional differences, population characteristics, or DRC program characteristics (e.g., types of programs, stipulations for completion, target population, and frequency or quality of contact with officers; see Caputo, 2004; Lanterman, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated a single DRC in a single county in a single state—what “happens in Vegas” may indeed “stay in Vegas.” Our study suggests DRCs can be effective, but it is clear from prior evaluations that DRCs are not always effective. It is not without reason that the title of a recent quasi-experimental evaluation of DRC programs in New Jersey begins with “Better to Stay Home…” (Hyatt & Ostermann, 2019). Variation across evaluations of DRCs could be due to a number of factors in addition to jurisdictional differences, population characteristics, or DRC program characteristics (e.g., types of programs, stipulations for completion, target population, and frequency or quality of contact with officers; see Caputo, 2004; Lanterman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest DRCs decrease recidivism (Champion et al, 2011;Rhyne & Hamblin, 2010). Others suggest DRCs have no effect or even increase recidivism (Boyle et al, 2013;Hyatt & Ostermann, 2019), while other studies suggest both the former and latter depending on moderating factors (Craddock, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, although one study found higher rearrest rates among prison releasees with no supervision (65.2 percent) than among parolees (50.7 percent) (Osterman, Saleron, and Hyatt 2015), this gap shrank when parole revocation was included in the definition of recidivism and disappeared entirely when controlling for demographics, offense, and a risk score (see also Jackson 1983). Other modes of community supervision, such as day reporting centers (which provide a combination of services and supervision), also have no effects on recidivism, or are associated with elevated rates of crime (Hyatt and Osterman 2019; Wong et al 2019).…”
Section: Reimagining Community Supervisionmentioning
confidence: 99%
“…Many jurisdictions deploy large arrays of treatment and programmatic resources for people on parole through the use of third-party contracted and noncontracted service providers (Boyle et al, 2013;Hyatt & Ostermann, 2019;Martin et al, 2003;Ostermann & Hyatt, 2017). These rehabilitative service providers typically seek to address criminogenic needs through cognitive-behavioral programming and may be accompanied by control-oriented supervision enhancements, such as day reporting centers (Boyle et al, 2013;Hyatt & Ostermann, 2019;Martin et al, 2003) and residential treatment centers (Ostermann, 2009;White et al, 2010). Even considering the theoretical constancy of RNR programming, assessments of correctional service providers and programs have indicated that they have a highly variable effect on recidivism rates.…”
Section: Rehabilitative Resources In Community Correctionsmentioning
confidence: 99%